The Moderating Effect of Gender in Urgent Care Service Satisfaction. Issue 3 (1st January 2017) - Qin, G; Boonme, Kittipong; George, Benjamin; Prybutok, Victor
Abstract : The objective of this study is to investigate the extent to which gender serves as a moderator in the relationships between healthcare service quality, patient satisfaction, and behavioral intention in the urgent care industry. Using the data collected from 253 male and 209 female urgent care patients, the moderating effect of gender was examined through partial least square structural equation modeling. Gender was found significant in the relationship between urgent care quality and patient satisfaction. To improve patient satisfaction among males, urgent care providers should focus on reducing negative emotions among male patients. This can be done by reducing the gap between their expectations and their perceptions, creating a warm environment in the urgent care facility, and alleviating patients' emotional vulnerability. The female community is more willing to pay a premium price and recommend the urgent care providers if they are satisfied. The practical implication is that urgent care providers should employ different strategies across gender to improve their perceptions of care quality and satisfaction level.